2017
DOI: 10.1038/s41467-017-00772-5
|View full text |Cite
|
Sign up to set email alerts
|

An HDAC3-PROX1 corepressor module acts on HNF4α to control hepatic triglycerides

Abstract: The histone deacetylase HDAC3 is a critical mediator of hepatic lipid metabolism, and liver-specific deletion of HDAC3 leads to fatty liver. To elucidate the underlying mechanism, here we report a method of cross-linking followed by mass spectrometry to define a high-confidence HDAC3 interactome in vivo that includes the canonical NCoR–HDAC3 complex as well as Prospero-related homeobox 1 protein (PROX1). HDAC3 and PROX1 co-localize extensively on the mouse liver genome, and are co-recruited by hepatocyte nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
79
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(80 citation statements)
references
References 72 publications
1
79
0
Order By: Relevance
“…6i, j). A previous study also reported that HNF4α could recruit additional cofactors to regulate gene expression 50 . In our study, around 90% of HNF4α binding sites were stable between carbohydrate-rich diet and lipid-rich diet group, which led us to hypothesize that Hnf4α co-binding with other transcription factors may play an important role in response to external stimuli and physiologic change.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…6i, j). A previous study also reported that HNF4α could recruit additional cofactors to regulate gene expression 50 . In our study, around 90% of HNF4α binding sites were stable between carbohydrate-rich diet and lipid-rich diet group, which led us to hypothesize that Hnf4α co-binding with other transcription factors may play an important role in response to external stimuli and physiologic change.…”
Section: Discussionmentioning
confidence: 91%
“…Using HOMER, we found that the Hnf4α binding motif was enriched in the promoter regions of DEGs, a finding validated by Hnf4α ChIP-seq. HNF4α is an orphan nuclear receptor involved in metabolic regulation with the potential to both activate and repress transcription 50,51 . In our study, we observed that nearly 80% of Hnf4α binding sites overlapped with H3K27ac enriched loci, which suggests that Hnf4α prefers to bind at regions of open chromatin.…”
Section: Discussionmentioning
confidence: 99%
“…Mice were genotyped by PCR of tail DNA as described in the above-mentioned papers. Validation of HNF4a depletion was shown by Armour and colleagues (Armour et al 2017).…”
Section: Animalsmentioning
confidence: 79%
“…PROX1 in lymphatic endothelial cells increases fatty acid oxidation during cell proliferation, and by interacting with p300 provides epigenetic regulation of lymphangiogenic gene expression (Wong et al, 2017). In hepatocytes, HDAC3–PROX1 interaction was found to be a major regulator for genes related to lipid homeostasis, and specific ablation of either component increased triglyceride content in the liver (Armour et al, 2017). In agreement with these results, PROX1 interacted with HDAC3 in RD cells, and PROX1 silencing led to lower fatty acid uptake and oxidation, accompanied by triglyceride accumulation, indicating that PROX1 also regulates tumor lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%